Design and fabrication of reliability test fixture for surface treatment test and peel off test - Sazwan, Sahar (2009)
In industry, the ability of a produced matter to stand for the outside force and other physical factor is the measurement for its quality. The same matter happened to printed labels which is exist on the structure of a product. These labels are exactly tested before the product could reach the market. The tests are, surface treatment test and the peel off tests, which is a sudden force is applied on the printed labels. In the mean time, the tests are tested by bare hands, which is without any help of machine. But, as we all know, tests which are conducted with bare hands, maybe will give effect to the result of the test which, the test have to bow on some disciple. This condition may cause an undesired result of test. So, the fabrication of the device will help the industry to overcome the problem of the limited ability of the human beings which will help in producing a test with good results.